Lehrfreiheit und Lehrbeanstandung - Härle, Wilfried; Leipold, Heinrich (Reader Theologie, 1985)
Bd. 1: Theologische Texte. -- 1985. -- 203 p. -- ISBN 3-579-00290-2. Bd. 2: Kirchenrechtliche Dokumente. -- 1985. -- 237 p. -- ISBN 3-579-00291-0.